2018
DOI: 10.1016/j.bpj.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Phase Coexistence in Biological Membrane: Insights from Local Nonaffine Deformation of Lipids

Abstract: Lateral heterogeneities in biomembranes play a crucial role in various physiological functions of the cell. Such heterogeneities lead to demixing of lipid constituents and formation of distinct liquid domains in the membrane. We study lateral heterogeneities in terms of topological rearrangements of lipids to identify the liquid-liquid phase coexistence in model membranes. Using ideas from the physics of amorphous systems and glasses, we calculate the degree of nonaffine deformation associated with individual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 92 publications
1
38
0
Order By: Relevance
“…Efficient lipid diffusion is a requirement for equilibrating domains or detecting protein-induced lipid sorting. Coarse-grained MD (CG-MD) has been used to great success in a number of simulations for both lipid-protein binding and membrane organization (103)(104)(105)(106)(107)(108) . Here we use CG-MD as a "computational microscope" to observe the equilibrium distribution of lipids local to the nAChR in a range of binary and ternary lipid mixtures inspired by native membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient lipid diffusion is a requirement for equilibrating domains or detecting protein-induced lipid sorting. Coarse-grained MD (CG-MD) has been used to great success in a number of simulations for both lipid-protein binding and membrane organization (103)(104)(105)(106)(107)(108) . Here we use CG-MD as a "computational microscope" to observe the equilibrium distribution of lipids local to the nAChR in a range of binary and ternary lipid mixtures inspired by native membranes.…”
Section: Introductionmentioning
confidence: 99%
“…7(D) show the L o and L d phases identified based on a cut-off on thickness and φ 6 respectively. While φ 6 is a good marker to distinguish between gel-fluid co-existing phases, we find that it is a poor marker to distinguish liquid-liquid co-existing phases [50]. The boundary marked in black in Fig.…”
Section: Choice Of Order Parameter and Boundary Profilesmentioning
confidence: 73%
“…Besides these commonly used markers, we also use the degree of non-affine displacements (χ 2 ) [49] to distinguish between the different phases in the lipid bilayer systems. We recently showed that χ 2 works as a high-fidelity marker between the liquid order (L o ) and liquid disordered (L d ) regions in the membrane system at molecular length scales [31,50,51]. χ 2 was originally applied on granular material by Falk and Langer ( [49]) and is given as:…”
Section: Order Parameters Used As Domain Boundary Classifiersmentioning
confidence: 99%
“…We then calculate the interaction energies between lipids as a function of a newly defined order parameter (χ 2 ) that utilizes the information on topological changes and displacements of neighbouring lipids to locally characterize the extent of order/disorder in the membrane without any knowledge of the chemical identity of the lipids. 74,75 Formulations and schematic related to measurement of non-affine (χ 2 ) value ( Figure S1a) and details of calculations of interaction energy ( Figure S1b) is discussed in the supporting information (SI). The χ 2 values of the three phase separated systems shows a bimodal distribution and is able to capture the ordered and disordered phases without the knowledge of chemical identity of the lipids ( Figure S2 and S3).…”
mentioning
confidence: 99%
“…This characterization was first used as a measure of shear stress propagation in metallic glasses to study irreversible plastic deformations 76 and have been extensively applied recently on soft matter systems 77-79 and on biological systems. 74,75,80,81 Figure S5 shows the calculated interaction energies for each lipid as a function of its χ 2 values for the three systems of interest. We observe that degree of positive correlation between lipid-lipid interaction energies and χ 2 values gradually decreases from DPPC/DOPC/CHOL to PSM/DOPC/CHOL and PSM/POPC/CHOL.…”
mentioning
confidence: 99%